Economic Transition and Poverty: The Case of the Vysehrad Group Countries - Adam Szulc (Luxembourg Income Study (LIS), 1996)
In this research, poverty in the Vysehrad Group countries (Czech Republic, Hungary, Poland and the Slovak Republic) is compared. Equivalent income is adopted as an individual welfare measure. Poverty indices are calculated using both absolute and relative poverty lines. Comparability across countries is enhanced by using purchasing power parities, estimated within a spatial consumer demand system. The highest poverty incidence was found for Poland and the lowest for the Czech Republic. Unemployment, low education and female head result in significant risk of poverty in all four countries.
Keywords: 330